Pivotal Role of TNF-α in the Development and Progression of Nonalcoholic Fatty Liver Disease in a Murine Model - Kakino, Satomi; Ohki, Tsuyoshi; Nakayama, Hitomi; Yuan, Xiahong; Otabe, Shuichi; Hashinaga, Toshihiko; Wada, Nobuhiko; Kurita, Yayoi; Tanaka, Kayo; Hara, Kento; Soejima, Eri; Tajiri, Yuji; Yamada, Kentaro (Hormone and Metabolic Research, 2018)
Previously, we have shown that the adipocyte-specific nuclear form of sterol regulatory element-binding protein-1c (nSREBP-1c) transgenic mice spontaneously developed hepatic lesions that are similar to those of human nonalcoholic steatohepatitis (NASH) with a concomitant elevation of plasma TNF-α. In this study, we analyzed the role of TNF-α in the progression of nonalcoholic fatty liver disease (NAFLD). We established a Tnf knockout nSREBP-1c transgenic mouse line. Glucose tolerance and liver histology were examined at the age of 20 weeks. The gene expression and protein levels were assessed by quantitative RT-PCR and Western blot, respectively. The Tnf knockout improved glucose tolerance and significantly reduced the prevalence of hepatic steatosis (20% vs. 100%, p<0.0001) and fibrosis (15% vs. 65%, p=0.0057). The expressions of Acaca, Scd1, Mcp1, Tgfb1, Col1a1, and Timp1 were increased in the liver from the original nSREBP-1c transgenic mice. However, gene upregulation was reduced in the livers from the Tnf(−/−) nSREBP-1c transgenic mice. Furthermore, the hepatic levels of TIMP1 protein were increased in the original nSREBP-1c transgenic mice but not in Tnf(−/−) nSREBP-1c transgenic mice. To assess the direct effect of TNF-α on the expression of the genes, we cultured primary hepatocytes in the presence of TNF-α and found that TNF-α increased the expression of Mcp1, Tgfb1, and Timp1 in hepatocytes. These observations indicate that TNF-α plays a pivotal role in the development of NAFLD and progression to NASH through upregulating key molecules associated with lipid metabolism, inflammatory cytokines, and fibrosis in the liver.
Keywords: nonalcoholic steatohepatitis; liver fibrosis; MCP1; TGF-β; TIMP1